Perbandingan Kualitas Pelayanan Bank Syariah Dengan Bank Konvensional Di Yogyakarta Bagi Nasabah Ganda Menggunakan ‘Carter’ Model - Wijiharta Wijiharta (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2010)
The aim of this study is to investigate the level of service quality of Syariah Bank which is compare between Conventional Bank services quality, used 6 dimensions CARTER model (Othman Owen, 2001). The subject of this research is a people who have an account  in Syariah Bank and also have account in Conventional Bank. This research takes a place in Yogyakarta. The result of this research indicated that service quality based on 6 dimension CARTER model in Syariah Bank more higher really than Conventional Bank  with  range 0,3275 from 5 Likert scale (6,55%). If based on 5 dimension SERVQUAL model (without Compliance dimension) there is no difference between Syariah Bank and Conventional Bank in service quality. Compliance dimension in Syariah Bank more higher really than Conventional Bank with range 2,24 from 5 Likert scale (44,8 %). In the other way, Assurance, Reliability, Tangibles, Empathy, and Responsiveness dimensions there are no differences  real.